A CRISPR/Cas12a-based portable platform for rapid detection of Leptosphaeria maculans in Brassica crops - Lei, Rong; Li, Yuan; Li, Limei; Wang, Jingyi; Cui, Zhenhai; Ju, Rui; Jiang, Li; Liao, Xiaoling; Wu, Pinshan; Wang, Xinyi (Frontiers in Plant Science, 2022)
Establishing a portable diagnostic method for plant pathogen is essential to prevent the spread of plant disease, especially in field and customs inspections. Leptosphaeria maculans (L. maculans) is an aggressive fungus leading to severe phoma stem canker of Brassica napus, which is responsible for major yield losses of oilseed rape worldwide. In this study, CRISPR/Cas12a based detection system and recombinase polymerase amplification (RPA) technique were employed to develop a rapid and sensitive detection method for L. maculans. The involved RPA pre-amplification and CRISPR/Cas12a cleavage confer considerable sensitivity and selectivity, which can be finished within 45 min with a LOD of 4.7 genomic DNA copies. This detection system was further developed to two portable platforms, i.e. one-pot lateral flow detection and all-in-one chip lateral flow assay (AOCLFA), which integrates the lyophilized recombinase polymerase amplification (RPA) reagents and lyophilized Cas12a cleavage reagents in one tube or chip. The developed portable platforms have flexible portability and simple operation for the detection of L. maculans from plant tissues in field. The proposed portable suitcase containing the minimum equipment, regents and AOCLFA meets the practical needs of rapid on-site disease screening of plant fungi, or port quarantine, or pathogen spreading control.